ANALISIS ADAB MENUNTUT ILMU PERSPEKTIF KITAB ALALA DAN RELEVANSINYA DENGAN PENDIDIKAN KARAKTER - Gizka Ardiani Nihaya; Hawin Fitriyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The world of education has recently faced real challenges related to the moral decline of learners. This symptom is evident from the fading respect for teachers, the rise of an instant learning culture, and the weak persistence of learners in going through the learning process. This study aims to analyze the six requirements for seeking knowledge in the Kitab Alala Tanalul 'Ilma (Anonim, n.d.), a pesantren poetry book that summarizes the core thoughts from the tradition of Kitab Ta'lim al-Muta'allim. The six aspects examined include intelligence (dzaka'), passion (hirsh), patience (istibar), provision (bulghah), teacher's guidance (irsyadu ustadzin), and a long period of time (thulu zaman). All of these components are dissected to see their relevance to strengthening the character of learners in the modern era. Using a qualitative literature study approach with content analysis and hermeneutic interpretation methods, this study shows that the six requirements form a unified character that supports each other. These elements are not limited to being technical requirements or formal administrative matters in learning, but are a real manifestation of the ethics of seeking knowledge (adab menuntut ilmu) that guides how learners appreciate knowledge, respect teachers, and enjoy their learning process. To strengthen its analysis, this study connects the concepts in Kitab Alala with Thomas Lickona's character education theory which covers the realms of moral knowing, moral feeling, and moral action. The results of the analysis find structural harmony proving that Kitab Alala offers a classic character education model that remains applicable to address the moral crisis issues of today's young generation.